THE INFLUENCE OF FINANCIAL RISK ON BANK STOCK RETURN IN MALAYSIA - Lau Yun, Yi; Sharifah Sabrina, Syed Ali; Bakri, Abdul Karim (UNIMAS Publisher, 2025)
This study investigates how financial risk influences the stock returns of Malaysian banks listed on Bursa Malaysia from 2015 to 2024. Using a multivariate Generalized Least Squares regression model, the effects of credit risk, market risk, liquidity risk, and capital risk on quarterly bank stock performance were examined. The analysis leverages data from nine major listed banks, controlling for multicollinearity, heteroscedasticity, and autocorrelation. The findings reveal that among the four risk measures, only the capital-to-asset ratio has a statistically significant positive impact on stock returns, indicating that stronger capitalization enhances investor confidence. Credit, market, and liquidity risks do not show significant effects, suggesting market efficiency in incorporating public information. These results offer insights for investors, bank management, and regulators to improve risk mitigation strategies and bolster financial stability in Malaysia's banking sector.